Neck circumference as an anthropometric marker of overweight among school-aged children in Bharatpur, Nepal: A community-based study - Subina Bajracharya; Sadikshya Neupane; Parita Shrestha (PLoS ONE, 2026)
Background Childhood overweight have become a major public health concern among children in developing countries. BMI, commonly used to diagnose overweight, requires standardized equipment and trained personnel, limiting their feasibility in large-scale screenings. Neck circumference (NC) has emerged as a simple and practical alternative for identifying overweight in children. This study aimed to examine the association between NC and established anthropometric indicators and to determine optimal NC cutoff values for identifying overweight among school-aged children. Methods A community-based descriptive cross-sectional study was conducted from July to October 2025 among 300 apparently healthy children aged 6–11 years in Ward No. 16, Bharatpur Metropolitan City, Nepal. Sociodemographic data were collected using structured interviews. Anthropometric measurements including height, weight, NC, waist circumference (WC), and hip circumference (HC) were obtained using standardized procedures. BMI-for-age classifications were based on WHO AnthroPlus growth references. Chi square test, pearson correlation, logistic regression, and receiver operating characteristic (ROC) curve analyses were performed using SPSS version 16. Statistical significance was set at p < 0.05. Results Among the 300 children, 48.3% had normal BMI-for-age, 10.3% were overweight and 41.3% were underweight. Chi square test revealed a statistically significant association between neck circumference and BMI-for-age (p < 0.001). Pearson correlation analysis demonstrated strong positive correlations between NC and weight (r = 0.792), height (r = 0.639), BMI (r = 0.723), waist circumference (r = 0.797), and hip circumference (r = 0.734) (p < 0.001 for all). ROC curve analysis indicated excellent diagnostic accuracy of NC for identifying overweight. The optimal cutoff values were 27.75 cm for boys (AUC = 0.884; sensitivity = 88.9%; specificity = 66.2%) and 26.75 cm for girls (AUC = 0.904; sensitivity = 100%; specificity = 69.4%). The overall cutoff value was 27.25 cm (AUC = 0.883; sensitivity = 80.6%; specificity = 74.3%). Multivariable logistic regression analysis confirmed NC had a statistically significant positive association with overweight with COR 12.077 (4.75–30.67) and AOR 20.817 (6.34–68.29). Conclusions Neck circumference is significantly correlated with established anthropometric indicators and demonstrates diagnostic accuracy for identifying overweight among school-aged children. NC measurement is a simple, reliable, and cost-effective screening tool that may be particularly useful in school-based and resource-limited settings.